A RECORD OF WEEVIL (COLEOPTERA: CURCULIONOIDEA) DIVERSITY FROM DISTRICT SAMBA (J & K) - J. S TARA; SUNIL SHARMA; RAMNIK KOUR (The Bioscan, 2010)
The present study was undertaken to record the weevil diversity of District Samba of Jammu and Kashmir State. Extensive survey of the region was conducted during the year 2008-09 to record the diversity of weevils. A total of nine species of weevils (superfamily Curculionoidea) viz. Cylas formicarius, Alcidodes signatus, Alcidodes collaris, Xanthochelus faunus, Apion sp., Odoiporous longicollis, Lixus truncatulus, Myllocerus discolor, Phytoscaphus sp. were collected, preserved and identified from IARI, New Delhi. Further studies with regard to their diagnostic features are also incorporated in this communication.